O03.6 Vaginal bacteria and risk of incident and persistent infection with high risk sub-types of human papillomavirus. (14th July 2019) - Carter, Kayla; Srinivasan, Sujatha; Kimani, Joshua; Anzala, Omu; Kabare, Emmanuel; Shafi, Juma; Brown, Elizabeth; Fredricks, David; Mcclelland, R; Balkus, Jennifer
Abstract : Background: Certain vaginal bacteria may increase women's risk for infection with high risk sub-types of human papilloma virus (hrHPV). The role of vaginal bacteria in hrHPV persistence is less well studied. We assessed associations between vaginal bacteria and hrHPV acquisition and persistence among Kenyan women in the placebo arm of the Preventing Vaginal Infections trial. Methods: Nonpregnant, HIV-uninfected women aged 18–45 from Kenya and the United States were enrolled in a randomized trial of periodic presumptive treatment to reduce vaginal infections over 12 months. Genital fluid specimens collected at enrollment and every 2 months thereafter were tested for 14 hrHPV types using the Hologic APTIMA HPV assay. Quantitative PCR targeting the 16S rRNA gene from ten bacteria was used to measure bacterial concentrations in vaginal swabs. Multivariate multinomial logistic regression and multistate Markov models restricted to Kenyan placebo participants were used to assess associations between log10-transformed bacterial concentrations (categorized in tertiles) and hrHPV acquisition and persistence. Results: Among the 84 Kenyan placebo participants, hrHPV was detected in 79/563 specimens (14%), with 16 episodes of persistent hrHPV (detection in > 2 consecutive specimens; median duration was 6 months). Controlling for age, hormonal contraceptive use, and condom use, Lactobacillus jensenii concentration was positively associated with hrHPV incidence (adjusted odds ratio (aOR)=1.57; 95% CI 1.07–2.30); and Atopobium vaginae (aOR=1.40; 95% CI 1.02–1.93), Megasphaera species (aOR=1.39; 95% CI 1.03–1.88), and Mageeibacillus indolicus (aOR=1.48; 95% CI 1.09, 2.02) concentrations were positively associated with hrHPV persistence. BV (Nugent score > 7) was not significantly associated with hrHPV incidence or persistence. Multistate Markov models did not indicate that bacterial concentrations were associated with transitions between HPV detection states. Conclusion: These findings suggest that higher concentrations of certain vaginal bacteria may increase risk of hrHPV incidence and persistence. Future work with more frequent sampling could provide additional insight into factors associated with hrHPV persistence. Disclosure: No significant relationships.